5-3x=-11+x

Simple and best practice solution for 5-3x=-11+x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5-3x=-11+x equation:


Simplifying
5 + -3x = -11 + x

Solving
5 + -3x = -11 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
5 + -3x + -1x = -11 + x + -1x

Combine like terms: -3x + -1x = -4x
5 + -4x = -11 + x + -1x

Combine like terms: x + -1x = 0
5 + -4x = -11 + 0
5 + -4x = -11

Add '-5' to each side of the equation.
5 + -5 + -4x = -11 + -5

Combine like terms: 5 + -5 = 0
0 + -4x = -11 + -5
-4x = -11 + -5

Combine like terms: -11 + -5 = -16
-4x = -16

Divide each side by '-4'.
x = 4

Simplifying
x = 4

See similar equations:

| -x+38=2x+17 | | 8(x+4)+10=10x-2(x-5) | | 7.84cm= | | 7.84= | | -2x+14=x+2 | | x^2+7x+36.75=0 | | 3x-2=20-x | | 4-2c=8 | | -5x-29=145 | | (4x+3)*(3x+2)=0 | | x+6x-1=90 | | (4x-3)*(3x-2)=0 | | 3(2q+3)=5(2q+1) | | -log(x)=20 | | 4x^2+3x+12=12 | | 3(5c-1)-2=13c+13 | | 5x/6-2=3 | | -3x+23=x+3 | | 60x+70y=4200 | | 3(5x-3)-3(2x-5)= | | A-(-3)=25 | | sin(40)=12/x | | y/-9=4 | | x^6-2x^3-4=0 | | 19m+23n+-3n= | | 2x-27=312 | | 7x-19+3x+9=180 | | -(5x-3)-3(2x-5)= | | (4x-6)/3=-2 | | 6*8*18= | | 0.49=cos(x) | | -7(3p+2)40=3(5p+6) |

Equations solver categories